Late talkers: Vocabulary intervention for a three year old - Eydal, Marta; Einarsdóttir, Jóhanna T.; Karlsson, Þorlákur; Úlfsdóttir, Þóra Sæunn (Menntavísindasvið Háskóla Íslands, 2019)
Late talkers are children who have low expressive vocabulary and/or do not use two word sentences at the age of two years. Approximately 15% of children between 2 and 3 years of age are classified as late talkers and at risk of developing language disorder. Developmental language disorder (DLD) in children is characterized by problems with language that cannot be explained by neurological, cognitive, sensory or emotional factors. The prevalence of DLD in five year old children is approximately 7%. Around half of the children identified as late talkers will later acquire language within the normal range but approximately half of the others will later be diagnosed with language disorder. At the age of two years it is not known which children will later be diagnosed with DLD. Language disorders may cause social and learning problems later in life. Early intervention, where a child receives appropriate evidence based intervention, can have positive effects on language development. Almost all children in Iceland attend preschool between the ages of 2 and 3 and spend on average seven hours in school each day, five days a week. Preschool teachers play a key role in advising and educating parents on language development. However, they do not have an official role in systematically screening early language to identify children at risk of being late talkers. Additionally, early intervention for children under three years of age is not systematically organized. Intervention for this age group is limited in Iceland. Early intervention for young children needs to be defined and organized so that each child can be serviced according to his/her needs.The aim was to investigate whether a cross-situational learning method was successful to improve vocabulary knowledge in a late talker. The intervention was based on the presentation of a few predetermined target words administered with intensity using a different variable method. The subject heard the target words 64 times or more in each session. Control words were also chosen ...